Structure-function relationships of the peptide Paulistine: A novel toxin from the venom of the social wasp Polybia paulista - Gomes, Paulo Cesar; de Souza, Bibiana Monson; Dias, Nathalia Baptista; Brigatte, Patrícia; Mourelle, Danilo; Arcuri, Helen Andrade; dos Santos Cabrera, Marcia Perez; Stabeli, Rodrigo Guerino; Neto, João Ruggiero; Palma, Mario Sergio [UNESP] (Elsevier, 2014)
Background: The peptide Paulistine was isolated from the venom of wasp Polybia paulista. This peptide exists under a natural equilibrium between the forms: oxidised - with an intra-molecular disulphide bridge; and reduced - in which the thiol groups of the cysteine residues do not form the disulphide bridge. The biological activities of both forms of the peptide are unknown up to now. Methods: Both forms of Paulistine were synthesised and the thiol groups of the reduced form were protected with the acetamidemethyl group [Acm-Paulistine] to prevent re-oxidation. The structure/activity relationships of the two forms were investigated, taking into account the importance of the disulphide bridge. Results: Paulistine has a more compact structure, while Acm-Paulistine has a more expanded conformation. Bioassays reported that Paulistine caused hyperalgesia by interacting with the receptors of lipid mediators involved in the cyclooxygenase type II pathway, while Acm-Paullistine also caused hyperalgesia, but mediated by receptors involved in the participation of prostanoids in the cyclooxygenase type II pathway. Conclusion: The acetamidemethylation of the thiol groups of cysteine residues caused small structural changes, which in turn may have affected some physicochemical properties of the Paulistine. Thus, the dissociation of the hyperalgesy from the edematogenic effect when the actions of Paulistine and Acm-Paulistine are compared to each other may be resulting from the influence of the introduction of Acm-group in the structure of Paulistine. General significance: The peptides Paulistine and Acm-Paulistine may be used as interesting tools to investigate the mechanisms of pain and inflammation in future studies. © 2013 Elsevier B.V.
Keywords: Disulphide bridge; Hyperalgesia; Inflammation; Molecular structure; Pain; Wasp venom